Предмет: Математика,
автор: rommanova1983
-(9,77- 6 5/9)-(0,23-1 4/9)=?
Приложения:
Ответы
Автор ответа:
0
Ответ:
Пошаговое объяснение:
=-9,77+6 5/9-0,23+1 4/9=2
-9,77-0,23=-10
6 5/9+1 4/9=8
-10+8=2
Автор ответа:
0
Ответ: -2.
Пошаговое объяснение:
-(9,77- 6 5/9)-(0,23-1 4/9)=1993/450.
1) -( 9,77- 6 5/9)=-( 977/100-59/9)= -(8793-5900)/900 = -2893/900;
2) 0,23-1 4/9=23/100-13/9=(207-1300)/900= -1093/900;
3) -2893/900-( -1093/900)=-2893/900+1093/900=1800/900= -2.
Похожие вопросы
Предмет: Русский язык,
автор: киса90
Предмет: Русский язык,
автор: йцукергшщзхъ
Предмет: Русский язык,
автор: marksman51015
Предмет: Английский язык,
автор: maslovae483
Предмет: Биология,
автор: manara3